Scalable Galaxy Morphology Classification through Hybrid Handcrafted and Deep Learning Approaches - Neves, Murilo L. C.; Policante, Maria Eduarda M.; Feltrim, Valéria D.; Costa, Yandre M. G. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
The rapid growth of astronomical surveys has transformed galaxy morphology classification into a large-scale data analysis problem that requires automated and scalable machine learning solutions. In this work, we evaluate handcrafted and deep learning approaches using a balanced subset of the Galaxy Zoo 2 dataset containing seven morphological classes. We first investigate the impact of a multi-step preprocessing pipeline and extract handcrafted descriptors capturing textural, morphological, intensity, and structural properties of galaxies. These descriptors are evaluated using classical machine learning models, including SVM, MLP, Random Forest, and KNN. We then assess convolutional neural networks (AlexNet, ResNet50, MobileNetV2, and EfficientNetB0) using transfer learning on both preprocessed and raw centrally cropped images. Finally, we explore a hybrid ensemble combining handcrafted and deep representations. The best configuration, based on a weighted soft-voting scheme, achieved an F1-score of 0.929. These results indicate that handcrafted descriptors and deep representations capture complementary information, and that their integration can improve scalable scientific image analysis in data-intensive research environments.